Dry graphene transfer print to polystyrene and ultra-high molecular weight polyethylene − Detailed chemical, structural, morphological and electrical characterization. (May 2015) - Lock, Evgeniya H.; Delongchamp, Dean M.; Schmucker, Scott W.; Simpkins, Blake; Laskoski, Matthew; Mulvaney, Shawn P.; Hines, Daniel R.; Baraket, Mira; Hernandez, Sandra C.; Robinson, Jeremy T.; Sheehan, Paul E.; Jaye, Cherno; et al.
Abstract: Graphene (Gr)–polystyrene (PS) and graphene (Gr)–ultra-high molecular weight polyethylene (UHMW PE) laminates were fabricated using a transfer print approach that relies on differential adhesion to remove graphene from Cu foil without chemical etching. The polymer surfaces were prepared using plasma functionalization followed by N-ethylamino-4-azidotetrafluorobenzoate (TFPA) deposition. Then, the graphene on Cu foil and the TFPA coated polymers were pressed at elevated temperature and mild pressure. Finally, they were separated by mechanical peeling. No additional processing was applied. Detailed chemical, structural, and morphological characterization of PS and UHMW PE before and after graphene transfer print was performed using a suite of complementary surface analysis techniques including X-ray Photoelectron Spectroscopy (XPS), Near Edge X-ray Absorption Fine Structure Spectroscopy (NEXAFS), Raman Spectroscopy, and Atomic Force Microscopy (AFM). The charge carrier density and charge carrier mobility of the transferred graphene were determined using Hall effect measurements. We found that graphene's electrical properties were preserved and comparable to those of graphene on SiO2 /Si. Furthermore, modulation of TFPA attachment to PS and UHMW PE led to different TFPA-layer microstructure and therefore to a different amount of functional azide groups available to form carbene bonds with graphene causing changes in graphene's compressive strain, doping and mobility.